Locating causes of accidents in the social organisation of building workers and some wider implications: an approach from Cultural Theory. (30th September 2005) - Mars, Gerald
This paper overviews and re-interprets accident causation in the British Building and Construction Industry (BCI), chosen because its accident rate is high. The paper, a preliminary report of ongoing work, suggests why incidences vary widely between different sites and workgroups. Explanation appears to lie not in variant technical complexity but variant social organisation. Four archetypal forms of organisation are identified derived from Cultural Theory via social anthropology that avoid personality explanations, and focus on micro social organisation. Different kinds of micro social organisation are known to differentially influence attitudes to authority and risk-taking, views of time, filtering of information and deviance. This approach focuses on the social side of socio-technical systems when most commentators over-emphasise the technical and it is also appropriate to more technologically complex industries. The paper concludes with a plea to collect accident statistics with emphasis on micro social components and offers a method – LISTORG – to order the social dimensions involved.